Carbon materials from melamine sponges for supercapacitors and lithium battery electrode materials: A review. Issue 2 (30th October 2019) - Shi, Yanying; Liu, Guijing; Jin, Rencheng; Xu, Hui; Wang, Qingyao; Gao, Shanmin
Abstract: With the increasing energy demand together with the deteriorating environment and decreasing fossil fuel resources, the development of highly efficient energy conversion and storage devices is one of the key challenges of both fundamental and applied research in energy technology. Melamine sponges (MS) with low density, high nitrogen content, and high porosity have been used to design and obtain three‐dimensional porous carbon electrode materials. More importantly, they are inexpensive, environment‐friendly, and easy to synthesize. There have been many reports on the modification of carbonized MS and MS‐based composites for supercapacitor and lithium battery electrode materials. In this paper, recent studies on the fabrication of electrode materials using MS as raw materials have been mainly reviewed, including carbonation, doping activation, and composite modification of MS, and expectations for the development of porous carbon materials for energy storage as a reference with excellent performance, environment‐friendliness, and long life. Abstract : Melamine sponges (MS) with high nitrogen content and porosity have been used to design three‐dimensional porous carbon electrode materials. There have been many reports on the modification of carbonized MS and MS‐based composites for supercapacitor and lithium battery electrodes materials. This paper reviewed the recent studies on the fabrication of electrode materials by using MS as raw materials, including carbonation, doping activation, and composite modification.